STRATEGI CEGAH TANGKAL JARINGAN TERORIS DALAM REKRUTMEN DAN SELEKSI PEGAWAI BARU PERTAMINA HULU ENERGI NUNUKAN COMPANY - Muhammad Roy Urich Kusumawardana; Ningky Sasanti Munir (Research Center and Case Clearing House PPM School of Management, 2020)
The terrorism threat nowadays is a formidable challenge due to the phenomenon of terrorist perpetrators that are actually part of company employees. Thus, selecting and recruiting new employees process is a strategic matter in preventing the entry of terrorist networks into the company. PHENC which is a national vital object and subsidiary of the oil and gas company, PT Pertamina (Persero), has the potential to become a terrorist operational target. It refers to the statements of the ex-combatants interviewed in this study. The terrorist team have data of pipelines, wells, oil and gas refineries throughout Indonesian companies. Therefore, PHENC needs to have a strategy to prevent the terrorism network in the recruitment and selection of new employees. This study is applied research using qualitative and narrative approach with detailed situation of the research object. Qualitative data were collected by written interview method with PHENC management representatives and using descriptive analysis techniques. The analysis result shows that currently PHENC has not conducted Background Check in the recruitment and selection process of new employees. Based on the PHENC risk register, recruitment and selection are listed as secutity threat risks. The design of the proposed strategy to prevent the terrorism network in recruitment and selection of new employees consists of three parts: part for new permanent employees, for new outsourcing employees and the implementation of integrated security management system (SMS).